Interdependence of roles, role rotation, and sense of community in an online course. Issue 1 (2nd January 2017) - Jiang, Wenting
Abstract: More and more educational institutions are moving towards online distance learning. Although asynchronous online learning overcomes the constraints of time, place and pace, online distance learners feel isolated due to the lack of real-time communications. One possible solution for overcoming this sense of isolation is regulating student online behavior by assigning specific roles and protocols for participation to learners in order to stimulate online learning activities. This qualitative study explored the use of such a technique in a fully online class in order to find out how the interdependence of roles and role rotation support a sense of community among learners. Data was collected through observations, discussion archives, surveys, and interviews. The results indicate that interdependent roles and role rotation provide students diverse learning experiences and interdependence in different ways. Students' tendency to depend on their classmates and to participate is enhanced when using the starter-wrapper with roles technique.